2012
DOI: 10.4018/jide.2012100104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mergers on Bank Competitiveness in Nigerian Banking Industry

Abstract: An inclusive merger mechanism became one option for the Nigerian banking industry in response to a Central Bank of Nigeria’s policy to increase the minimum paid-up share capital requirement of Nigerian banks from N2 billion to N25 billion in July 2004, with December 31, 2005 as deadline. More than half of the 89 banks in Nigeria as at July 2004 were engaged in one form of merger. The study objective gives insight into the effectiveness of economic policy reforms in the Nigerian banking industry. This study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However Taiwo et al (2016), aver that the cashless policy, which was adopted in Nigeria in June 2012, has created a burden for uneducated, the underprivileged, and non-exposed traders. Verifiable records as claimed by Adekoya (2011), cited in Ikpefan & Omankhanle (2012) revealed that the informal sector controls a sizable quantity of liquidity and cash in circulation. Even with the greatest of intentions, the move is undermined by a sizable population that is barely literate and an economy that lacks social institutions to support such policies at this time.…”
Section: Issues/prospects In Nigeria's Cashless Policymentioning
confidence: 97%
See 1 more Smart Citation
“…However Taiwo et al (2016), aver that the cashless policy, which was adopted in Nigeria in June 2012, has created a burden for uneducated, the underprivileged, and non-exposed traders. Verifiable records as claimed by Adekoya (2011), cited in Ikpefan & Omankhanle (2012) revealed that the informal sector controls a sizable quantity of liquidity and cash in circulation. Even with the greatest of intentions, the move is undermined by a sizable population that is barely literate and an economy that lacks social institutions to support such policies at this time.…”
Section: Issues/prospects In Nigeria's Cashless Policymentioning
confidence: 97%
“…Even with the greatest of intentions, the move is undermined by a sizable population that is barely literate and an economy that lacks social institutions to support such policies at this time. Ikpefan & Omankhanle (2012).…”
Section: Issues/prospects In Nigeria's Cashless Policymentioning
confidence: 99%
“…The increase in the number of banks is, itself, a positive development because more people access and become aware of banking services than before. However, this accelerated expansion has stretched regulators to the hilt, weakened the effect and scope of regulatory oversight and eased the standards of accountability and corporate governance (Ikpefan and Odularu, 2007). This has opened up the sector to insider abuses, undesirable practices and executive self-indulgences such as corrupt diversion of funds by contract staff, customer cash suppression, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several works have focused on studying stock market; including examining market efficiency (Lahmiri et al, 2014;Lahmiri, 2013aLahmiri, , 2014aLahmiri, , 2014bLahmiri, , 2015Lahmiri, , 2016aLahmiri, , 2016bLahmiri, , 2016c, modeling and forecasting market prices (Lahmiri, 2011;Lahmiri, 2012bLahmiri, , 2012cLahmiri & Boukadoum, 2015), and investigating the effects of technology and governance on market behavior (Ikpefan & Oligbo, 2012;Narang, 2012;Choudhury, 2013;Shaw et al, 2014). Besides, the linkage between asset risk and return is an interesting issue in portfolio management and corporate finance that merits deeper investigation in emergent markets.…”
Section: Introductionmentioning
confidence: 99%